2018
DOI: 10.1111/scd.12324
|View full text |Cite
|
Sign up to set email alerts
|

Oral hygiene and dentition status in children and adults with hemophilia: A case–control study

Abstract: Background & objectives:People with hemophilia constitute a significant proportion of the population and an oral health care professional faces a considerable challenge while treating them. This study aimed to assess the oral health and dentition status as well as fear of dental treatment in patients with hemophilia and compare it with age-matched healthy subjects. Patients & methods:This single-center, case-control cross-sectional study was performed on 100 subjects with hemophilia and 100 age-matched healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(48 citation statements)
references
References 12 publications
1
46
1
Order By: Relevance
“…Like COPD, oral diseases are also often associated with comorbidities 34,50,[59][60][61][62][63] . The inclusion of oral health into treatment plans has benefited patients across the lifespan who are living with chronic diseases 34,50,59-63 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Like COPD, oral diseases are also often associated with comorbidities 34,50,[59][60][61][62][63] . The inclusion of oral health into treatment plans has benefited patients across the lifespan who are living with chronic diseases 34,50,59-63 .…”
Section: Resultsmentioning
confidence: 99%
“…The inclusion of oral health into treatment plans has benefited patients across the lifespan who are living with chronic diseases 34,50,59-63 . One case-control study concerning the inclusion of oral healthcare for patients with hemophilia makes a comparison with healthy individuals and reveals that hemophilic patients had higher debris and calculus scores, suggestive of poor oro-dental health status 59 . The perception of childhood obesity as being a medical rather than dental issue, as well as dentists' unwillingness to suggest interventions due to the fear of being offensive and judgemental, has led to many missed opportunities for screening childhood obesity at the dental office 50 .…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have reported an increase in the dmft/DMFT scores of young hemophilia patients [65][66][67]. However, other reports found comparable caries indices in hemophilia patients as in healthy individuals [68,69]. In fact, even a lower prevalence of caries has been shown in young hemophilia patients compared to the general population of Northern Ireland [70].…”
Section: Coagulation Defects and Oral Healthmentioning
confidence: 99%
“…Prolonged bleeding after tooth extraction may also occur in women who are carriers of hemophilia [ 34 ]. The cause of bleeding in the oral cavity, in addition to the deficiency of the coagulation factor, may be poor hygiene associated with the fear of possible mechanical injury, thus leading to gingivitis [ 35 ]. There are discrepancies in dental health and oral hygiene in individuals with CBD [ 29 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…The cause of bleeding in the oral cavity, in addition to the deficiency of the coagulation factor, may be poor hygiene associated with the fear of possible mechanical injury, thus leading to gingivitis [ 35 ]. There are discrepancies in dental health and oral hygiene in individuals with CBD [ 29 , 35 ]. The literature reports a frequent occurrence of osteoporosis in patients with hemophilia [ 36 , 37 ], as well as the possibility of complications related to hemorrhages into muscles and joints [ 38 ].…”
Section: Introductionmentioning
confidence: 99%